MENTORING CHILDREN TO LEARN AT HOME IN DISTANCE LEARNING DURNG THE COVID-19 PANDEMIC IN TASIKMALAYA CITY - Lilis Karwati; Ahmad Hamdan (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2022)
Learning activities during the pandemic are carried out online at home, of course it is the responsibility of the family, especially parents, to accompany the child during home study. Parents should be prepared to accompany and guide their children learning from home. People play a role in accompanying and guiding children during online learning, parents must also understand the applications used during online learning.  This research is qualitative phenomenology research, it aims to analyze children's learning assistance during distance learning during the Covid-19 pandemic in Tasikmalaya City. The data collection techniques used in this study are interviews, observations and documentation. The subjects of this study were parents of children who did online learning. The results showed that during the pandemic almost the entire primary school (SD) in Tasikmalaya city learning was conducted online. Learning carried out online has several problems, namely the limitations of teachers in delivering materials that make the child do not understand the material in its entirety, parents should increase the cost of spending on internet costs during online learning. Learning at home accompanied by parents makes the child closer to the parents, the child feels safe and comfortable being close to the parents so that the child becomes more confident.